Study on the Effect of Floating Impeller Axial Displacement on the Performance and Axial Force of Vortex Pumps - W. F. Yang; R. H. Zhang; X. Y. Wang; G. Q. Guo (Journal of Applied Fluid Mechanics)
The impact of the axial displacement of a floating impeller in a vortex pump on performance and axial force was investigated through numerical simulations, validated by experimental tests. Simulations were conducted to calculate axial forces at various impeller positions under different operating conditions. The results indicate that increasing the axial displacement of the impeller reduces both the pump head and efficiency. Compared with inlet axial clearance, reducing the outlet axial clearance improves energy conversion while having a smaller effect on head performance. At lower flow rates, the pressure difference between the balance cavities on both sides of the floating impeller increases, leading to a higher axial force. Adjusting the axial position of the impeller can effectively reduce axial force, optimising both its magnitude and direction to help restore the impeller to a central position. The balance cavity modifies the static pressure distribution in the high-pressure region of the impeller, further minimising extreme axial force values in this region. However, as flow rate increases, the influence of the balance cavity diminishes.